Досвід Німеччини в програмуванні протидії злочинності в сучасних умовах - Титаренко, О. О.; Tytarenko, O. O. (Право і суспільство. - 2019. - № 4. - С. 267-274, 2019)
Розглянуто досвід Німеччини в програмуванні протидії злочинності в сучасних умовах. Встановлено, що останнім часом у країні фіксується поступове зниження рівня злочинності, що пояснюється ефективною реалізації державної політики в протидії злочинності, яка відображається у відповідних стратегічних та програмних документах.

The article describes the experience of Germany in the programming of countering crime in modern conditions. It has been established that recently in the country a gradual decrease in the level of crime has been fixed, which is explained by the effective implementation of the state policy in combating crime, which is displayed in the relevant strategic and program documents. It is substantiated that there has recently been observed a certain symbiosis of the implementation of the classical model (primary, secondary and tertiary prevention) of crime prevention and the neoclassical model, which includes: developmental prevention, community prevention, situational prevention. The specificity of anticrime programming is determined by the federal structure of the country. Great powers in the field of counteraction crime have federal lands. In the formation of program documents on combating crime at different levels and the introduction of relevant projects and initiatives, an approach is taken both from the "top-down" (on the most pressing issues of the fight against crime) and from “bottom to top”. In Germany, crime prevention is mandatory at all three levels: federal, state and municipal. Unlike other EU countries, Germany has a strong, well-coordinated network of actors involved in the formation and implementation of crime prevention policies (governmental, non-governmental organizations, coordination groups, prevention councils, academic institutions, civil society). A significant influence on the formation of a federal strategy in the field of combating crime and related programs has: National Center for Crime Prevention (NZK), the German Crime Prevention Forum (DFK), the German Crime Prevention Congress (DPT), the Crime Prevention Councils of the Federal States. The main emphasis in the formation of crime prevention programs is placed on their implementation at the local level, depending on the existing problems, with wide public involvement, which is consistent with the common еuropean approaches. The possibility of borrowing the German experience for Ukraine in programming such activities through a system of interested subjects is substantiated.

Рассмотрен опыт Германии в программировании противодействия преступности в современных условиях. Установлено, что в последнее время в стране фиксируется постепенное снижение уровня преступности, что объясняется эффективной реализации государственной политики в противодействии преступности, отражающейся в соответствующих стратегических и программных документах.
Keywords: протидія злочинності; crime counteraction; противодействие преступности; програмування; programming; программирование; програми профілактики; prevention programs; программы профилактики; зарубіжний досвід; foreign experience; зарубежный опыт; Німеччина; Germany; Германия